Innovation in ecological restoration techniques: Enhancing Portulacaria afra survivorship in degraded arid thicket - Norman, Yondela Masande (Rhodes University, Faculty of Science, Department of Environmental Science)
The Albany Thicket Biome has undergone extensive degradation over the past century, particularly from overstocking of livestock in the arid types of thicket. The degradation of the biome, coupled with little to no natural recovery, prompted the South African Government to implement the Subtropical Thicket Restoration Programme (STRP) in the early 2000s to rehabilitate degraded thicket using unrooted Portulacaria afra truncheons. The STRP also sought to create job opportunities, bring about social upliftment, promote biodiversity conservation and incentivise farmers and landowners in the region to promote carbon trading and farming of P. afra using carbon credits. However, the survivorship of P. afra planted using the STRP planting protocol has been less than â “30% because they are planted in degraded areas, where the truncheons are subjected to harsh biophysical conditions such as hard, capped soil, high soil temperatures, drought and herbivory. The aim of this study, therefore, was to improve the survivorship of P. afra planted in degraded thicket to at least 30%, using modified planting methods. In this study, four treatments were applied in 210 pondings (or micro-dams), each with P. afra planted in them (the first three treatments used rooted cuttings). The first treatment involved watering regimes where pondings were watered at varying frequencies. The second treatment involved planting companion species alongside P. afra while the third treatment involved planting P. afra underneath a nurse canopy. In the fourth treatment, unrooted P. afra truncheons were planted inside pondings. The mean survivorship of the P. afra cuttings was assessed 18 months after planting. The watering regime treatments, including the control, all yielded a survivorship of over 75%, with the significantly highest levels of survivorship being displayed in the weekly watering treatment (90.9 Â± 6.8%) (p < 0.01). The companion plant treatment also produced a high mean survivorship of P. afra (94.9 Â± 3.6%), significantly higher than that of the nurse plants (87.5 Â± 6.3%) (p < 0.01). Among the unrooted truncheons it was found that untreated truncheons had the highest survivorship (76.2 Â± 17.6%), with the lowest mean being found in truncheons that were both pruned and scarified (70.8 Â± 20.8%), suggesting that this treatment, out of all of them, is the least successful under the prevailing environmental conditions in the study area. However, there was no significant differences among the unrooted truncheon treatments and their respective survivorship values to further substantiate this assertion (p = 0.26). Findings in this study also suggest that planting P. afra cuttings under a nurse plant was ideal for P. afra survivorship due to the nurse plant's ability to ameliorate the microclimate under which the cuttings can establish and grow. Despite the soil under the nurse canopy having a significantly lower mean soil water potential (-160.9 Â± 200.5 kPa), compared to the open areas (-73.4 Â± 55.7 kPa) (p = 0.04), the pondings under the nurse canopy still had a lower mean soil temperature (31.4 Â± 5.25Â°C) than the treatments in the open areas (38.5 Â± 2.7Â°C), during the harsh midday sun. These favourable characteristics are reflected in the P. afra cuttings under a nurse canopy having a higher chlorophyll fluorescence (0.76 Â± 0.06). compared to those planted in open areas (0.73 Â± 0.13), suggesting that the P. afra cuttings in the former treatment had a higher photosynthetic efficiency compared to those in the latter, despite there being no statistically significant difference in chlorophyll fluorescence between the treatments (p = 0.14). Although these findings suggest that applying these modifications to planting P. afra, having achieved its objective of increasing survivorship to well over 50%, is likely to produce favourable results not only in overall survivorship, but also in fast-tracking arid thicket rehabilitation and restoration, further research on these rehabilitation techniques and their effectiveness is required. Furthermore, the downside to these treatments is that they are costly and time consuming, which puts the feasibility of large-scale programmes using these applications into question. Further investigation is required to determine ways in which the cost-effectiveness of these applications can be enhanced.
Keywords: Land degradation -- South Africa; Subtropical Thicket Ecosystem Planning; Portulacaria afra; Restoration ecology; Nurse plants